2005
DOI: 10.1159/000088724
|View full text |Cite
|
Sign up to set email alerts
|

Food-Additive-Induced Urticaria: A Survey of 838 Patients with Recurrent Chronic Idiopathic Urticaria

Abstract: Background: Recurrent chronic idiopathic urticaria (RCIU) is a common skin condition that affects 0.1–3% of the population in the USA and Europe and accounts for nearly 75% of all ‘ordinary’ chronic urticaria (CU) cases. Methods: We studied 838 consecutive patients with RCIU referred to hospital between 1998 and 2003. Patients with known causes of CU were excluded. Clinical history, physical examination, and symptom diaries were evaluated during two periods, a diet-free period (1 week) and a food-additive-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 70 publications
(87 reference statements)
2
49
0
1
Order By: Relevance
“…A recent oral double-blind, placebo-controlled food challenge (DBPCFC) study with common food additives in patients with CIU using semiquantitative skin scores as the end point produced positive reactions at rates little different than those seen with placebo. 168 The most recent study, using semi-quantitative skin scores as the end point, concluded the prevalence of food additive sensitivity in CIU patients occurs rarely if at all. 169 These include challenges with monosodium glutamate (MSG), benzoates, parabens, sulfites, butylated hydroxyanisole/butylated hydroxytoluene (BHA/BHT), tartrazine (FD&C Yellow #5, E102), Sunset yellow (FD&C Yellow #6, E110), and aspartame (Nutrasweet).…”
Section: Section V: Adverse Reactions To Food Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent oral double-blind, placebo-controlled food challenge (DBPCFC) study with common food additives in patients with CIU using semiquantitative skin scores as the end point produced positive reactions at rates little different than those seen with placebo. 168 The most recent study, using semi-quantitative skin scores as the end point, concluded the prevalence of food additive sensitivity in CIU patients occurs rarely if at all. 169 These include challenges with monosodium glutamate (MSG), benzoates, parabens, sulfites, butylated hydroxyanisole/butylated hydroxytoluene (BHA/BHT), tartrazine (FD&C Yellow #5, E102), Sunset yellow (FD&C Yellow #6, E110), and aspartame (Nutrasweet).…”
Section: Section V: Adverse Reactions To Food Additivesmentioning
confidence: 99%
“…168,169 Summary Statement 17: Do not routinely instruct asthmatic patients to avoid sulfites or other food additives unless they have a prior reaction to sulfites. Sulfites are the only food additive proved to trigger asthma.…”
Section: Section V: Adverse Reactions To Food Additivesmentioning
confidence: 99%
“…In other patients, aspirin and/or nonsteroidal anti-inflammatory drugs (NSAIDs) and/or food additives hypersensitivity can aggravate urticaria. However, in many patients the mechanisms causing their urticaria remain obscure [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Pseudoallergens include artificial food dyes, preservatives, and sweeteners, aromatic compounds in wine, tomatoes, and spices 8 ; as well as phenols, such as D-hydroxy benzoic acid, citrus and orange oil, and salicylates. 9 The remission rate attributed to elimination diets varies from 30% to 90%, yet double-blind, placebo-controlled food challenges with these substances have failed to reproduce urticaria, 10 and patients whose chronic urticaria has remitted can eat anything without becoming symptomatic. The right conclusion is that foods or additives do not contribute to the pathogenesis of chronic urticaria.…”
mentioning
confidence: 99%